The rate structure and capital movements: a note on operation twist - ROWAN, D. (PSL Quarterly Review, 2013)
The work looks at whether interest rate adjustments desirable for cyclical purposes can be made in a form which limits or discourages the outflow of capital. As a result of the widely accepted hypothesis that capital movements are primarily functions of short-term rates while aggregate demand is a a function primarily of long-term rates, it is often suggested that low rates at long-term should be accompanies by high rates at short-term. This implies that the reduction in long-rates should be carried out in a way that narrows the long-short differential. One such attempt along these lines was “Operation Twist”, conducted by the U.S. authorities after the 1960-61 recession. That policy is briefly re-examined and its impact on capital flows from the U.S. is assessed. JEL: E43, E58, F32